Topical Artocarpus communis Nanoparticles Improved the Water Solubility and Skin Permeation of Raw A. communis Extract, Improving Its Photoprotective Effect - Chun-Yin Yang; Pao-Hsien Huang; Chih-Hua Tseng; Feng-Lin Yen (MDPI AG, 2021)
Antioxidants from plant extracts are often used as additives in skincare products to prevent skin problems induced by environmental pollutants. Artocarpus communis methanol extract (ACM) has many biological effects, such as antioxidant, anti-inflammatory, wound healing, and photoprotective effects; however, the poor water solubility of raw ACM has limited its applications in medicine and cosmetics. Topical antioxidant nanoparticles are one of the drug-delivery systems for overcoming the poor water solubility of antioxidants for increasing their skin penetration. The present study demonstrated that ACM-loaded hydroxypropyl-β-cyclodextrin and polyvinylpyrrolidone K30 nanoparticles (AHP) were successfully prepared and could effectively increase the skin penetration of ACM through changing the physicochemical characteristics of raw ACM, including reducing the particle size, increasing the surface area, and inducing amorphous transformation. Our results also revealed that AHP had significantly better antioxidant activity than raw ACM for preventing photocytotoxicity because the AHP formulation increased the cellular uptake of the ACM in UVB-irradiated HaCaT keratinocytes. In conclusion, our results suggest that AHP may be used as a good topical antioxidant nanoparticle for delivering ACM into deep layers of the skin for preventing UVB-induced skin problems.